PHOTOEMISSION METHOD OF TEMPERATURE MEASURING IN THE PROCESS OF SPARK PLASMA SINTERING POWDERS OF REFRACTORY METALS - D. V. Minko; O. O. Kuznechik (Приборы и методы измерений, 2015)
Construction and algorithm of the photoemission pyrometer based on a photomultiplier are outlined; the calibration procedure is set out. The application of the photoemission method in a rapidly changing temperature is showed. It is proved that during spark plasma sintering the maximal temperature is 5500– 7500 °C, while the speed of temperature increase to its maximum ~108–109 °C/s, and the rate of decrease to 2000–4000 °C may be 106–107 °C/sec. It is recommended to use photoemission method when developing technological conditions, adjustment and control of technological processes using modern high-energy equipment (plasma, laser, cathode-ray tube) to produce new materials, coatings and products for mechanical engineering, electronic industry and medicine.